Efektivitas Penggunaan Media Audiovisual terhadap Keterampilan Menulis Teks Eksposisi Siswa SMP - Puspita, Dela; Septyanti, Elvrin; Permatasari, Silvia (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
Learning media is a tool to optimize the delivery of material in learning. The aim is so that students do not get bored and lose focus when the teacher delivers material if they only use print media. One of them is audiovisual media which contains images and sound (video). Therefore, researchers are interested in conducting research with the title,